Pemberdayaan Masyarakat Melalui Pelatihan Kepemimpinan dan Teknologi Informasi dalam meningkatkan Produktifitas Kelompok Usaha Desa Cibatu - Rezeki, Fitri; Permana , Indra; Sunaryati , Titin; Hadikristanto, Wahyu; Wulandari, Siska (PT. Alahyan Publisher Sukabumi, 2024)
Desa Cibatu has significant natural resource potential but faces considerable challenges in maximizing local economic growth, particularly in leadership, management, and technology adaptation. This research focuses on interventions through leadership and information technology training to enhance local capacity. Activities include intensive training in strategic decision-making, financial management, digital marketing, business mentoring and consulting. The results show a significant improvement in leadership and business management skills and an understanding of technology use. Quantitatively, there was a 15% reduction in the unemployment rate and an average 10% increase in per capita income. These findings confirm that a comprehensive and collaborative approach to local capacity development can optimize the village's economic potential, reduce unemployment, and improve community welfare. Designed interventions must be adaptive and sustainable to provide significant long-term impacts.